1993
DOI: 10.1111/j.1365-2621.1993.tb03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Compounds Formed on Prolonged Heating of Citrinin under Watery Conditions

Abstract: Citrinin was partially decomposed by heating under aqueous conditions at 90°C for 5 10 min and a group of degraded compounds (Group I) was detected by TLC. At 100°C and llO"C, citrinin disappeared rapidly, and the cytotoxicity of the samples increased with prolonged heating. At 12o"C, citrinin disappeared more rapidly while TLC spots of Group I compounds also diminished upon ~20 min heating and a new group of compounds (Group II) appeared. Cytotoxicity decreased rapidly at > 120°C and was eliminated after 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Several studies have been carried out on degradation of citrinin revealing that decomposition of citrinin occurs at > 175 °C under dry conditions, and at > 100 °C in the presence of water. Known decomposition products include citrinin H 2 which did not show significant cytotoxicity, while the decomposition product citrinin H 1 , which is made up of two citrinin molecules (Figure 1), showed an increase in cytotoxicity as compared to the parent compound (Trivedi et al, 1993a;Trivedi et al, 1993b;Hirota et al, 2002;Xu et al, 2006). Another decomposition product, the cytotoxic citrinin dimer, dicitrinin A, was also reported in 2006, together with other monomeric and dimeric degradation products (Clark et al, 2006).…”
Section: Chemistrymentioning
confidence: 95%
“…Several studies have been carried out on degradation of citrinin revealing that decomposition of citrinin occurs at > 175 °C under dry conditions, and at > 100 °C in the presence of water. Known decomposition products include citrinin H 2 which did not show significant cytotoxicity, while the decomposition product citrinin H 1 , which is made up of two citrinin molecules (Figure 1), showed an increase in cytotoxicity as compared to the parent compound (Trivedi et al, 1993a;Trivedi et al, 1993b;Hirota et al, 2002;Xu et al, 2006). Another decomposition product, the cytotoxic citrinin dimer, dicitrinin A, was also reported in 2006, together with other monomeric and dimeric degradation products (Clark et al, 2006).…”
Section: Chemistrymentioning
confidence: 95%
“…These results correlate with previous reports relating to cytotoxity tests of citrinin, heated under various conditions, toward HeLa cells. 9) Citrinin is unstable and thermolabile in water. It degrades on heating above 809 C under aqueous conditions.…”
mentioning
confidence: 99%
“…This indicates that heating of citrinin in water at 1409 C or 1509 C caused formation of a highly toxic compound(s). 9) We were interested in clarifying the degradation compounds of citrinin and tried to purify the degradation products and obtained a product, citrinin H1, with potent cytotoxic activity. 10) Further examination of the decomposition products from the heated citrinin led to the isolation of another product, citrinin H2.…”
mentioning
confidence: 99%
“…The selection of target mutants in the mutagen‐induced mutagenesis method is normally time‐consuming and is difficult to continue consecutive improvement due to the lack of understanding of the random mutation site; also the genetic mutation for Monascus species is mainly executed at the laboratory level for fundamental research, and no industrial application has been reported . Physical methods such as high‐temperature treatment can produce transformed products such as citrinin H 1 , which is ten times more toxic than citrinin, and citrinin H 2 , the major product with lower toxicity . Also filtration and adsorption as physical methods could have an influence on sensorial quality .…”
Section: Introductionmentioning
confidence: 99%